Enhancing junior high school students’ learning outcomes in ecology and biodiversity through problem-based learning (PBL) and culturally responsive teaching (CRT) - Rahmawati, Lusi; Agustina, Lina (Assimilation: Indonesian Journal of Biology Education, 2025)
Science learning at the junior high school level still faces various challenges, one of which is the tendency to emphasize memorization over deep conceptual understanding. Topics such as ecology and biodiversity are often considered less engaging for students, leading to lower learning outcomes. The Problem-Based Learning (PBL) model offers a solution by providing learning experiences that focus on solving real-life problems. Additionally, the Culturally Responsive Teaching (CRT) approach allows students to connect learned concepts with their culture and environment, making learning more meaningful. This study aims to examine the effectiveness of implementing a PBL model integrated with CRT in improving science learning outcomes on ecology and biodiversity topics among seventh-grade junior high school students. The study employs a quasi-experimental design with a posttest-only control group. Data were collected through a posttest to assess cognitive learning outcomes and observations during the learning process to evaluate affective learning outcomes. The findings indicate that in the experimental class, the average posttest score (79.79) surpassed that of the control class (63.88). A t-test analysis revealed a significant difference between the two groups (0.001 0.05). Furthermore, observations of the affective aspect indicated that student engagement and participation in the experimental class were higher than in the control class. These findings reinforce that the Problem-Based Learning (PBL) model integrated with Culturally Responsive Teaching (CRT) not only enhances cognitive understanding but also optimally fosters students' affective engagement compared to conventional learning methods.